Disorders of Speech Development and Communication of the Child with the Asperger Syndrome: A Case Study - Przybyla, Olga; Wons, Justyna (Logopedia Silesiana, 2018)
The article presents the tasks of speech therapy and the planned activities undertaken to support the communication development of the child with the Asperger syndrome. An attempt to describe communication disorders and the relationship with the aforementioned therapy is based on the selected case study. The article also presents such issues as the development of the child’s motor skills, the medical documentation, and the results of specialist and authors’ research.